Proceedings of the International Conference on Banking, Accounting, Management, and Economics (ICOBAME 2018) 2019
DOI: 10.2991/icobame-18.2019.20
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Motive, Product Quality, Price Perception and Brand Image toward Buying Decision Process

Abstract: This purpose of this study is to analyze the effect of motive, product quality, price perception and brand image toward buying decision process of Samsung smartphone. The population in this study were consumers who made a purchasing of Samsung smartphone in Semarang, Indonesia. The number of samples studied were as many as 100 people were selected as respondents using convenience sampling technique. Data collection methods used in this study was questionnaire filled out by respondents. The analysis method used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…The results of the T-test analysis indicate that the buying decision process of McDonald's customers on the BTS menu is influenced individually by customer perceptions, motivation, memory and emotion. Several previous studies have also shown the same results, such as Widyasari et al (2018), Bahrainizad andRajabi (2018), andQazzafi (2020) for the perception variable; Amron (2018) and Qazzafi (2020) for Memory variables; Auf et al (2018), Herawati et al (2019), Qazzafi (2020) for motivation variable; and Qazzafi (2020), Sungpo and Tun (2020), Jiseon and Jookyung (2022) for Emotion variable. Meanwhile, other 9 variables have no significant effect on buying decisions individually.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The results of the T-test analysis indicate that the buying decision process of McDonald's customers on the BTS menu is influenced individually by customer perceptions, motivation, memory and emotion. Several previous studies have also shown the same results, such as Widyasari et al (2018), Bahrainizad andRajabi (2018), andQazzafi (2020) for the perception variable; Amron (2018) and Qazzafi (2020) for Memory variables; Auf et al (2018), Herawati et al (2019), Qazzafi (2020) for motivation variable; and Qazzafi (2020), Sungpo and Tun (2020), Jiseon and Jookyung (2022) for Emotion variable. Meanwhile, other 9 variables have no significant effect on buying decisions individually.…”
Section: Discussionsupporting
confidence: 59%
“…This value indicates that the contribution of the independent variables on the dependent variable is 66.30%. While the rest of the other effects (33.70%) are caused by other variables, which are not examined in this study, such as product quality and price (Widyasari et al, 2018), work, lifestyle and psychology (Qazzafi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Because > 1.96 with a p-value> 0.05, so the fourth hypotesis cannot be admitted. This is backed up by the previously study which cites that perceived price does not affect brand image (Widyasari et al, 2019). Consumers may be more likely to prioritize other factors, such as product quality, other customer experiences, or other factors not used in this study, before forming an opinion about a brand, thus demonstrating that price perception does not influence brand image.…”
Section: Discussionmentioning
confidence: 55%
“…Menurut (Sadrabadi et al, 2018) (5) Brand Ambassador adalah perantara antara manajemen merek internal dan eksternal, yang secara signifikan dapat mempengaruhi persepsi pelanggan terhadap merek dan organisasi dan secara umum Brand Ambassador yang memperkuat merek reputasinya. Brand Ambassador ini merupakan salah satu bentuk komunikasi pemasaran yang atraktif dan ampuh untuk menggiring calon konsumen, nyaris semua brand akan berlomba-lomba untuk menetapkan Brand Ambassador paling happening (Widyasari et al, 2019) (6). Tingginya antusiasme masyarakat Indonesia terhadap boyband korea khususnya BTS, membuat perusahaan menggaet boygroup BTS sebagai bintang iklannya atau Brand Ambassador dari e-commerce Tokopedia (Safitri et al, 2021) (7).…”
Section: Aunclassified